Stress modeling for the upper and lower crust along the Anninghe, Xianshuihe, and Longmenshan Faults in southeastern Tibetan plateau - Xu, Junshan; Zeng, Xiangfang (Frontiers in Earth Science, 2024)
Earthquake occurrence depth in the crust is related to stress, temperature, and brittle–ductile transition, which is also near the transition depth of the upper to lower crust. The composition variation between the upper and lower crust causes remarkable changes of rheological properties and variation in stress distribution. Clarifying the detailed stress distribution in the upper and lower crust is crucial for understanding the brittle–ductile transition and the stress environment of the seismogenic zone. The Southeastern Tibetan Plateau (SETP), with wide spread of active strike−slip faults and clustered earthquakes, provides a natural field for investigating the relationships between crustal stresses, deformation behaviors, and earthquake mechanics. By considering the rheological properties of granite and anorthite, this paper established stress models with different boundary depths (15, 20 and 25 km) between the upper and lower crust along the Anninghe, Xianshuihe, and Longmenshan Faults in the SETP with a horizontal strain of 6 × 10−4 extracted from in situ stress data. The stress model with different geothermal gradients and a boundary depth of 20 km between the upper and lower crust suggests two distinct types of the brittle–ductile transition below these three faults. Simultaneously, the stress model can account for the continuity of earthquake depth distribution below the Longmenshan Fault and the seismic gap below the Anninghe and Xianshuihe Faults. The continuity of earthquake depth distribution or seismic gap below these three faults can be explained by their different geothermal gradients. These findings provide new insights for understanding the stress environment of the seismogenic zone in the SETP. Our model reveals the relationships between differential stress, seismicity, brittle–ductile transition, and boundary depth of the upper and lower crust in the continental crust, and connects the multiple observations from geophysics and geology. Furthermore, our model provides insights for studying multiple processes in the continental crust, such as crustal deformation, fault slip, and earthquake occurring.